Gilgamesh the Anti-Ulysses (Comparatismi, 2021)
This essay will address the Epic of Gilgamesh through the critical analysis that Theodor W. Adorno and Max Horkheimer theorized in reference to the Odyssey. The author intends to discuss an alternative point of view to the one proposed by the two Frankfurt philosophers, by examining in particular the first excursus of the Dialectic of Enlightenment, where Ulysses is defined as proto-bourgeois. The conclusion suggests a new interpretation that tries to reread the Dialectic of Enlightenment through the lenses of Gilgamesh’s vicissitudes.
Keywords: Gilgamesh; Ulysses; Adorno; Horkheimer; Enlightenment